'Remember the Sabbath': a history of technological decisions and innovation in Orthodox Jewish communities. (2nd April 2020) - Bix, Amy Sue
ABSTRACT: The relationship of Modern Orthodox Jewish communities to technology is mediated by the calendar, following requirements to keep the Sabbath holy. As nineteenth-, twentieth-, and twentyfirst-century inventions reshaped work, public spaces, and domestic living, rabbis intensely debated whether, how, and why observant Jewish people should avoid using electric switches, kitchen appliances, elevators, and other everyday devices on the Sabbath. To justify their decisions, rabbis interrogated minute technical details of these objects. Sabbath prohibitions promoted innovation, as rabbis collaborated with Jewish engineers to create what they judged to be Sabbath-compliant adaptions of everyday technologies. Given that prominent rabbis often disagreed about proper technology use on the Sabbath, Jewish families had the opportunity to decide for themselves what counted as authentic devotion in handling personal and domestic technologies.